Effects of quality grade, aging period, blade tenderization, and degree of doneness on tenderness of top sirloin butt steaks - C.D. George-Evins; John A. Unruh; James L. Marsden; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2000)
We used 162 top sirloin butts to determine the influence of different quality grades, postmortem aging periods, blade tenderization passes, and degree of doneness on thawing and cooking losses and Warner-Bratzler shear force (WBS, tenderness). Select (SEL), Choice (CHO), and Certified Angus Beef™ (CAB) top sirloin butts (n=54 for each) were aged for 7, 14, or 21 days and not tenderized (OX) or blade tenderized one (1X) or two (2X) times. Steaks from each top sirloin butt were assigned randomly to final endpoint cooking temperatures of 150, 160, and 170°F. Each longer aging period resulted in lower (P<.05, more tender) WBS. In addition, steaks blade tenderized 2X had lower (P<.05) WBS than steaks not tenderized or blade tenderized 1X. Within each quality grade, WBS increased (P<.05) as endpoint cooking temperature increased. When cooked to 160 or 170°F, CHO and CAB steaks had lower (P<.05) WBS than SEL steaks. Increased aging periods and blade tenderization passes of top sirloin butt steaks improved tenderness. When cooking to higher endpoint temperatures, using higher quality grades will minimize toughness caused by cooking.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Tenderness; Blade tenderization; Aging; Quality grade